Catalytic Synthesis of Acetone Direct Acetylene Hydration - N.I. Fayzullaev, A.R. Karjavov., S.S.Yusupova (International Journal of Advanced Science and Technology, 2020)
The article studies the reactions of acetone synthesis by direct hydration of acetylene on catalysts prepared from (Fe2O3)x : (V2O5)y: (ZnO)z : (Mn2O3)k, oxides, using an acetic acid solution as a peptizing agent. The main texture and operational characteristics of the synthesized catalysts are determined. Based on the study of the dependence of the degree of conversion, the stability of the catalyst and the yield of the target product on the water: acetylene ratio, it was found that the catalyst (Fe2O3)x : (V2O5)y: (ZnO)z : (Mn2O3)k worked stably for 125-144 h (provided that the temperature rises to 10°С every 20 hours). A technological scheme for producing acetaldehyde, acetone by catalytic hydration of acetylene is proposed.